2015
DOI: 10.1080/19440049.2014.996256
|View full text |Cite
|
Sign up to set email alerts
|

Physiological behaviour of gliotoxigenicAspergillus fumigatus sensu strictoisolated from maize silage under simulated environmental conditions

Abstract: Environmental conditions play a key role in fungal development. During the silage production process, humidity, oxygen availability and pH vary among lactic-fermentation phases and among different silage sections. The aim of this work was to study the physiological behaviour of gliotoxicogenic Aspergillus fumigatus strains isolated from maize silage under simulated natural physicochemical conditions - different water activities (a(W)), temperatures (Tº), pH and oxygen pressure - on the growth parameters (growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Other fungal species well adapted to ensilage conditions are Monascus ruber and Byssochlamys nivea . Recently, Alonso et al have studied toxigenic A. fumigatus strains isolated from maize silage and their gliotoxin production in vitro under environmental conditions as occurring in silage (i.e. water activity, temperature, pH and oxygen pressure).…”
Section: Fungal And/or Mycotoxin Contamination Of Silagementioning
confidence: 99%
“…Other fungal species well adapted to ensilage conditions are Monascus ruber and Byssochlamys nivea . Recently, Alonso et al have studied toxigenic A. fumigatus strains isolated from maize silage and their gliotoxin production in vitro under environmental conditions as occurring in silage (i.e. water activity, temperature, pH and oxygen pressure).…”
Section: Fungal And/or Mycotoxin Contamination Of Silagementioning
confidence: 99%
“…; Alonso et al . , ). Mathematical modelling can be a useful tool to predict, and consequently to prevent, the growth of mycotoxicogenic fungi and also to study their response to environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the prevention of fungal growth effectively prevents mycotoxin accumulation. Although some studies have determined the influence of environmental factors on the growth of A. fumigatus, none of them applied mathematical models to quantify these effects Alonso et al 2015Alonso et al , 2016. Mathematical modelling can be a useful tool to predict, and consequently to prevent, the growth of mycotoxicogenic fungi and also to study their response to environmental factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies (Alonso et al . ) demonstrated that A. fumigatus strains were able to grow at 25°C even if the availability of oxygen was reduced at very low pH (4–5). However, no studies have been conducted with A. fumigatus strains from silages to which farm workers are exposed.…”
Section: Introductionmentioning
confidence: 99%